Long-Term Results of Accelerated Corneal Cross-Linking in Adolescent Patients With Keratoconus. Issue 8 (August 2019) - Ozer, Muhammet Derda; Batur, Muhammed; Mesen, Selma; Tekin, Serek; Seven, Erbil
Abstract : Purpose: To report long-term results of accelerated corneal collagen cross-linking treatment in patients with progressive keratoconus in the pubertal period. Methods: Patients with progressive keratoconus aged 14 and younger were retrospectively reviewed. Thirty-five eyes of 23 patients, who were followed for at least 4 years postoperatively, were included in the study. Demographic characteristics, uncorrected visual acuity, best-corrected visual acuity, and corneal topography data were recorded. All patients underwent an epi-off accelerated corneal collagen cross-linking protocol. Results: The mean age of the participants was 13 ± 0.5 (11–14) years. Male to female ratio was 3/2. The mean pupillary center to cone apex distance was 1.6 ± 0.5 mm. At presentation, 11 eyes (31%) were classified as stage 1 keratoconus; 14 eyes (40%) were classified as stage 2 keratoconus, 8 eyes (23%) were classified as stage 3 keratoconus, and 2 eyes (6%) were classified as stage 4 keratoconus. The mean follow-up period was 56 ± 8 months. At the first year of the follow-up, central corneal thickness (CCT) and thickness of thinnest point of the cornea (TTPC) were found to be decreased significantly in comparison to preoperative values ( P = 0.02 and P = 0.003, respectively). At the second year of follow-up, only TTPC was found to be decreased in comparison to preoperative value ( P = 0.01). At the last follow-up visit, CCT was found to be increased significantly in comparison to preoperative CCT ( P = 0.04). Conclusions: After an average follow-up of 56 months, progression was determined in 20% of the eyes despite appropriate treatment. In the last visit, progression was found to be associated with K1, K2, CCT, TTPC, and age.